Quadruple Hydrogen Bonded Nanocarbon Networks for High Performance Dispersant-Free Conducting Pastes. Issue 1700 (2014) - Han, Joong Tark; Jang, Jeong In; Choi, Sua; Seo, Seon Hee; Jeong, Seung Yol; Jeong, Hee Jin; Lee, Geon-Woong
ABSTRACT: Colloidal dispersion of nanocarbon (NC) materials in dilute solutions or pastes is prerequisite for applications of NC-based electrodes from flexible electronics and flexible conducting fibers to electrochemical devices. Here, we show a straightforward method for fabricating NC suspensions with >10% weight concentrations in absence of organic dispersants. The method involves introducing supramolecular quadruple hydrogen bonding motifs into the NC materials without sacrificing the electrical conductivity.